COMMUNITY EMPOWERMENT THROUGH CULTIVATION TRAINING AND HERBAL DRINK POWDER PRODUCTION IN THE LEPROSY PATIENT FAMILY COMMUNITY - Handayani; Renny Novi Puspitasari; Gatot Kustyadji; Irvan Adhin Cholilie; Surya Iryana Ihsanpuro; Zahwa Salsabila; Rizka Ayu Salsabilla; Aina Izzatun Naila; Falih Dhiya’ulhaq; Muhammad Hefdi; Kurnia Farisya; Zumrotul Farikhah; Adityas Sabrina; Elysia Rahmayanti; Delivia Putri; Nur Vadiya; Adimas Indrayana; Muhammad Abadiyyusya; Muhammad Irfan Adi; Shabrina Zharfa; Retno Diah Putri Ekayanti (Community Service Journal of Indonesia, 2026)
Social stigma still attached to the families of leprosy patients in Sumber Glagah Hamlet, Pacet, Mojokerto, causes limited access to education, employment, and social interaction. This condition has led to a decrease in family income, even though leprosy is curable. To overcome this, community empowerment was carried out through cultivation training and the production of herbal drink powder as an effort to improve the economy and quality of life. The activity was conducted in Sumber Glagah Hamlet, Pacet District, Mojokerto. The methods used were counseling and training on the archipelago herbal drink (Serbat Nusantara) and the cultivation of herbal ginger plants. The total number of participants was 23 leprosy patient family members. The increase in participant knowledge was measured by giving a pre-test before the activity and a post-test after the training. The results showed a significant increase in knowledge, reaching a "Good" category score of 86.95%. Participants were very enthusiastic, demonstrated by their activeness during the discussion and question-and-answer session. This activity concludes that skill-based training, such as making herbal drink powder, can significantly increase the knowledge and morale of leprosy survivor families in economic empowerment efforts. It is suggested that similar programs be carried out sustainably and collaboratively to reduce stigma and strengthen local economic independence.